Design of low-noise LDO power supply for RF LNA - Song Fei (Dianzi Jishu Yingyong, 2018)
A power supply module is designed to supply RF low-noise amplifier(LNA) which is integrated in monolithic microwave integrated circuit(MMIC). The power supply module integrated in MMIC and uses a low dropout regulator(LDO) structure to produce a stable low noise voltage output. Due to the large noise of the traditional LDO structure, the circuit noise is reduced by the new structure combined with the voltage preconditioning and the RC low pass filter, and a fast start filter module is designed for the filter circuit. The simulation results show that the input voltage is 5 V, the output voltage is adjustable in the range of 1~4.2 V, the voltage output line regulation rate(LNR) is 8.2 mV/V, the load regulation rate(LDR) is 83.3 μV/mA, the output noise voltage in the range of 1 kHz～100 kHz integration of 34.94 μVrms, to meet the LNA power supply requirements.